UNRAVELING THE AMBIGUITIES IN UNDERSTANDING OF CSR IN THE BUSINESS WORLD: A PROFESSIONAL ETHICS PERSPECTIVE - Sachdev, Kumar Neeraj (PEOPLE: International Journal of Social Sciences, 2024)
The arguments regarding Corporate Social Responsibility (CSR) typically revolve around two main perspectives. Thinkers of one perspective assert that Individuals or Organizations should engage in CSR primarily because it is their moral obligation to work for the wellbeing of fellow human beings and the environment because they have the resources to help the people and the government. Thinkers of opposing viewpoint argue that Individuals or Organizations may refrain from participating in CSR initiatives because the primary objective of any business entity is to make profit and pursuit of any other objective is considered to be a waste of resources at the cost of investors. Both these viewpoints appear to form a no-meeting-point web of opposing arguments possibly because the definition of CSR and the perception about CSR generate a lot many ambiguities. The definition of CSR informs about voluntary assumption of responsibilities that go beyond economic and legal responsibilities but the examples of CSR appear to be varied: one moment, it seems to mean the use of corporate resources to operate a program to address some social problem; the next, it is all about charitable donations, and sometime later, it seems to mean providing benefits to employees to improve their quality of life in the workplace. On the other hand, the perception of people about CSR appears to be two-fold: CSR is a moral endeavor and CSR is a business strategy. The people working in the business world and elsewhere perceive CSR as a moral endeavor to help the general lot of people and the environment, but that is also perceived to function simultaneously as a business strategy to promote the economic interests of the organization. We argue in the paper that there is a need to better understand the conflicting domains of definition of CSR and perception about CSR separately and in relation to each other because any ambiguity in the understanding of these two aspects of CSR potentially can pose dangers to the ethically correct practices of CSR in the business world and in the society.